Candi, Space and Landscape A study on the distribution, orientation and spatial organization of Central Javanese temple remains - Degroot, Véronique (Mededelingen van het Rijksmuseum voor Volkenkunde, 2009)
Central Javanese temples were not built anywhere and anyhow. On the contrary: their positions within the landscape and their architectural designs were determined by socio-cultural, religious and economic factors. This book explores the correlations between temple distribution, natural surroundings and architectural design to understand how Central Javanese people structured the space around them, and how the religious landscape thus created developed. Besides questions related to territory and landscape, this book analyzes the structure of the built space and its possible relations with conceptualized space, showing the influence of imported Indian concepts, as well as their limits. Going off the beaten track, the present study explores the hundreds of small sites that scatter the landscape of Central Java. It is also one of very few studies to apply the methods of spatial archaeology to Central Javanese temples and the first in almost one century to present a descriptive inventory of the remains of this region.